The β Subunit of Voltage-Gated Ca(2+) Channels - Buraei, Zafir (Physiol Rev, 2010)
Calcium regulates a wide spectrum of physiological processes such as heartbeat, muscle contraction, neuronal communication, hormone release, cell division, and gene transcription. Major entry-ways for Ca((2+)) in excitable cells are high-voltage activated (HVA) Ca(2+)channels. These are plasma membrane proteins composed of several subunits, including α(1), α(2)δ, β, and γ. Although the principal α(1) subunit (Ca(v)α(1)) contains the channel pore, gating machinery and most drug binding sites, the cytosolic auxiliary β subunit (Ca(v)β) plays an essential role in regulating the surface expression and gating properties of HVA Ca((2+)) channels. Ca(v)β is also crucial for the modulation of HVA Ca((2+)) channels by G proteins, kinases, and the Ras-related RGK GTPases. New proteins have emerged in recent years that modulate HVA Ca((2+)) channels by binding to Ca(v)β. There are also indications that Ca(v)β may carry out Ca((2+)) channel-independent functions, including directly regulating gene transcription. All four subtypes of Ca(v)β, encoded by different genes, have a modular organization, consisting of three variable regions, a conserved guanylate kinase (GK) domain, and a conserved Src-homology 3 (SH3) domain, placing them into the membrane-associated guanylate kinase (MAGUK) protein family. Crystal structures of Ca(v)βs reveal how they interact with Ca(v)α(1), open new research avenues, and prompt new inquiries. In this article, we review the structure and various biological functions of Ca(v)β, with both a historical perspective as well as an emphasis on recent advances.